2020
DOI: 10.1542/peds.2019-1628
|View full text |Cite
|
Sign up to set email alerts
|

The Infantile Hemangioma Referral Score: A Validated Tool for Physicians

Abstract: and Troilius Rubin created the Infantile Hemangioma Referral Score tool, selected the 42 clinical cases for validating the tool (stage 1), and validated the study design; Drs van der Vleuten and Roessler participated in the validation of the gold standard (stage 2); and all authors discussed and validated the study results (including the choice of the threshold), reviewed and validated the manuscript, approved the final manuscript as submitted, and agree to be accountable for all aspects of the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 17 publications
1
53
0
2
Order By: Relevance
“…However, interrater reliability increased to substantial agreement at step 2 (use of IHReS) in both groups. The result correlated to the findings in the validation study of IHReS in 2020 3 and also reflected that the use of assisting instrument (IHReS) can help physicians in making their decision to refer patients with IHs for treatment. Our findings revealed that there was an increase in mutual agreement and acceptance after using IHReS not only among non-expert physicians-the IH experts also had benefited by the use of this score with an increased interrater reliability; Fleiss' Kappa in IHs experts were 0.42 at step 1 and 0.80 at step 2, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, interrater reliability increased to substantial agreement at step 2 (use of IHReS) in both groups. The result correlated to the findings in the validation study of IHReS in 2020 3 and also reflected that the use of assisting instrument (IHReS) can help physicians in making their decision to refer patients with IHs for treatment. Our findings revealed that there was an increase in mutual agreement and acceptance after using IHReS not only among non-expert physicians-the IH experts also had benefited by the use of this score with an increased interrater reliability; Fleiss' Kappa in IHs experts were 0.42 at step 1 and 0.80 at step 2, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…Léauté-Labrèze et al recently developed IHReS as an initial tool for primary care physicians to make their decision to refer patients to expert centres. 3 This is a two-step easy-to-use tool for non-expert physicians, provided with some drawing pictures indicating striking location and practical notice points in making decisions. This tool is free to use and is available to be downloaded from www.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for initiation of oral propranolol have evolved over time. [2][3][4][5][6][7][8][9] Consensus recommendations prior to the FDA/EMA approval in 2014 included the following 10 : (a) screening for contraindications to propranolol, (b) performing or obtaining documentation of, a recent normal cardiovascular and pulmonary history and examination, (c) obtaining key historical data including poor feeding, dyspnea, tachypnea, diaphoresis, wheezing, heart murmur, or family history of heart block or arrhythmia, and (d) prolonged in-office monitoring. The FDA/EMA-approved administration monitoring recommendations include in-office heart rate (HR) and blood pressure (BP) monitoring for 2 hours after the first dose of propranolol or for increasing the dose (>0.5 mg/kg/d) for infants 5 weeks of adjusted gestational age or older.…”
Section: Potential Risks Associated With Betablocker Treatmentmentioning
confidence: 99%
“…Recently, the Infantile Hemangioma Referral Score (IHReS) was developed, which is a tool for primary care providers, aiding decisions on which patients to refer 33 . It consists of 6–12 questions and can be completed online.…”
Section: Evaluation Of Infantile Haemangiomas and Patients/familiesmentioning
confidence: 99%